Influence of Friction Stir Welding Process on the Mechanical Characteristics of the Hybrid Joints AA2198-T8 to AA2024-T3 - Ahmed Samir Anwar Alemdar; Shawnim R Jalal; Mohammedtaher M Saeed Mulapeer (Advances in Materials Science and Engineering)
The study presents the hybrid joining of the third generation AA2198-T8 aluminum lithium alloy to AA2024-T3 aluminum copper alloy, which has been highly demanded recently in the aerospace industry. This investigation aims to reduce the cost of production in the industrial sector. As a result, an affordable alternative is to use hybrid designs using AA2198-T8 alloy in crucial parts and AA2024-T3 alloy in the rest of the structure. A joining method is required to create hybrid structures composed of last-generation and standard aluminum alloys. The joining process was successfully friction stir-welded using five different welding travel speeds—36, 76, 102, 146, and 216 mm/min—with an invariable spindle speed of 960 rev/min. Two reversed steps, double-sided friction stir welding (DS-FSW) and single-sided friction stir welding (SS-FSW) techniques with two appropriate tool designs, were employed to investigate the dissimilar material mechanical properties and their morphological changes. The experimental outcomes show that DS-FSW of the reversed steps has a higher joining strength than SS-FSW for all the welding parameters studied. The variation in travel speeds provided the highest strength at 102 mm/min travel welding speeds for DS-FSW. Therefore, it is found that, from the three tensile samples, tensile strength, yield strength, and elongation of the joint were 407.1 MPa, 271.2 MPa, and 9.5%, respectively. The joint efficiency reached 87% compared with the base material tensile strength of AA2024-T3. Furthermore, fractures of the tensile samples were found in the vicinity of the thermomechanically affected zone (TMAZ) of the AA2198-T8 side. The microhardness and morphology results correspondingly have precise predictions for the fracture zone of the joints in this research examination.